An Answer Verification Approach to Objective Questions in Intelligent Tutoring Systems - Wenzu Li (Цифровая трансформация)
An approach to develop a problem solver for automatic answer verification to objective questions in intelligent tutoring systems constructed using OSTIS (Open Semantic Technology for Intelligent Systems) technology is сonsidered. The problem solver is developed based on multi-agent technology within OSTIS. The proposed problem solver automatically verifies the correctness and completeness of the user’s answer at the semantic level by starting the corresponding sc-agent sets according to the type of the questions. The objective question answer verification is one of the main purposes of the developed problem solver, it can also perform the calculation of the similarity between any two semantic graphs.